2013
DOI: 10.2478/s11532-013-0295-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and chemical properties of Inula helenium root extracts

Abstract: The objective of the paper was to investigate the chemical composition of Inula helenium roots extracts and to evaluate the antioxidant potential conferred by the chemical constituents. GC/MS and HPLC/MS techniques were used to characterize two extracts separated from Inula helenium roots by extraction with chloroform and ethyl acetate, respectively. Volatile compounds have been identified by GC from their mass spectra and retention time values, while HPLC identification of phenolic compounds was realized by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
5
29
1
Order By: Relevance
“…These natural substances exhibit numerous biological activities [8][9][10] which explains the high content of phenolic compounds in food. This phenomenon is particularly evident in the case of extruded products enriched in herbs, cereals, vegetables and fruits with high content of poliphenolic antioxidants [35,36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These natural substances exhibit numerous biological activities [8][9][10] which explains the high content of phenolic compounds in food. This phenomenon is particularly evident in the case of extruded products enriched in herbs, cereals, vegetables and fruits with high content of poliphenolic antioxidants [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of dietary phenolic components for the prevention of some diseases and for health quality improvement has attracted much research attention in the last decade [6][7][8][9]. Polyphenols were found to exhibit a wide range of pharmacological properties, for example: neuroprotective, cardioprotective, anti-cancer and antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaiswal et al (2011) identified six hydroxycinnamic acid derivatives in the extract from aerial parts of I. helenium, including three monocaffeoylquinic acids (1-O-, 3-O-, and 5-O-CQA), 5-O-feruloylquinic acid, 5-O-p-coumaroylquinic acid, and 3-Ocaffeoyl-4-O-p-coumaroylquinic acid. According to Spiridon et al (2013), roots of the plant contained: caffeic acid, caffeic acid hexose of undetermined structure, 5-O-CQA, 5-O-feruloylquinic acid, ferulic acid-4-O-glucoside, DCQA (structure not determined), 3-O-feruloyl-4-O-caffeoylquinic acid, and 3,4,5-tri-O-caffeoylquinic acid. Our research revealed the presence of 16 caffeic acid derivatives in the examined tissue, whereas derivatives of ferulic and p-coumaric acids were absent from the analyzed calli.…”
Section: Resultsmentioning
confidence: 99%
“…Literature data concerning hydroxycinnamic acid derivatives present in I. helenium are sparse. It is only recently that some reports on analysis of extracts from leaves and roots of the plant using high performance liquid chromatography with mass spectrometry (HPLC/MS) and tentative identification of phenolic compounds have been published (Jaiswal et al 2011;Spiridon et al 2013). Callus cultures of I. helenium maintained in our laboratory showed high total phenolic content.…”
Section: Introductionmentioning
confidence: 96%